EVALUATION OF THE RESULT OF MAGNETIC RESONANCE IMAGING IN CHILDREN AND ADOLESCENTS WITH EPILEPSY, EXAMINED IN OUTPATIENT AND POLYCLINIC CONDITIONS - Umarova M.F., Jurabekova A.T. (Research Focus International Scientific Journal, 2025)
Epilepsy ranks 4th out of 220 diseases in terms of disability severity, where mortality in patients with epilepsy exceeds that of the general population by more than 3 times and ranks 25th in terms of sudden (emergency) death - SUDEN (Sudden Unexpected Death in Epilepsy). Clinical and pathogenetic study of epilepsy in children and adolescents: etiology, mechanism of formation, nature of epileptic seizures, transformation, complications, progression, polymorphism, hopelessness of epileptic disorders, drug resistance, all these issues, despite being comprehensively studied, require additional analysis, seem very important and relevant.